Organizational Commitment Can Improve Compliance of Blood Transfusion Procedure - Edi Murwani; Stefanus Supriyanto; Suharto Suharto (International Journal of Public Health Science (IJPHS), 2016)
The purpose of this research was to improve compliance of nurses and midwives on blood transfusion procedures through increased organizational commitment. The study used observational analytic with cross sectional approach. 156 nurses and midwives who meet the inclusion and exclusion criteria agreed to participates respondents and 46 observers agrees involved in the collection of data through informed consent. The sampling technique was simple random sampling. Data instrument collectors in the form of checklists and questionnaires. Analysis of the data used in the form of descriptive analysis, correlation, and Structural Equation Modeling (SEM). Based on the findings of a new model, a model compliance nurses and midwives on blood transfusion procedures, organizational commitment can improve compliance procedure of blood transfusion if affective commitment and normative commitment improved.